ÇRETU, Ana-Maria; MASSIMI, Michela (ed.) (2020). Knowledge from a human point of view, Springer - Hérnandez Pérez, Abraham (Daimon Revista Internacional de Filosofia, 2021)
Reseña de: ÇRETU, Ana-Maria; MASSIMI, Michela (ed.) (2020). Knowledge from a human point of view, Springer.